If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -3)(x + -9) = 0 Reorder the terms: (-3 + 3x)(x + -9) = 0 Reorder the terms: (-3 + 3x)(-9 + x) = 0 Multiply (-3 + 3x) * (-9 + x) (-3(-9 + x) + 3x * (-9 + x)) = 0 ((-9 * -3 + x * -3) + 3x * (-9 + x)) = 0 ((27 + -3x) + 3x * (-9 + x)) = 0 (27 + -3x + (-9 * 3x + x * 3x)) = 0 (27 + -3x + (-27x + 3x2)) = 0 Combine like terms: -3x + -27x = -30x (27 + -30x + 3x2) = 0 Solving 27 + -30x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(9 + -10x + x2) = 0 Factor a trinomial. 3((1 + -1x)(9 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Solution
x = {1, 9}
| 4(5+2)+2= | | 15x-28=-73 | | =-4x^2+5x-12 | | 7-1k=5+3k | | 18g+7=14g-9 | | 8x-12=3x+11 | | =4x^2-5x+12 | | 5a-8a+3a= | | -2d+18-4d=16 | | 2+3y=8 | | 3.3q-2.9-4.8q=2.5q-4.9 | | 6+b=7 | | 15d-8-3d=16 | | (2x^3+3x^2-1)=0 | | (3b-2)(3b^3+6b^2+2)= | | 7x=14+15x | | 4(y+4)=5(y-3) | | 6.7+12m-9.3=6.2 | | 91-3x= | | 2x*4=8 | | 2x^2+2y^2-xy+15x+30=0 | | x-15=-28 | | x^3-6x-16=0 | | (4x+3)(2x-4)= | | p^2-7p=28 | | (4x-1)/6+(2x+1)/2=2 | | 10x-9-9=14x-9+6x | | 15n+15+4n=130 | | x^2+7c+10=0 | | x+12=21 | | 4k^2-125=5k | | 7-k=5+3k |